How Do Investors Respond to Targets’ Interim Earnings? - Gunn, Rita; Pierce, Spencer; Romney, Miles (The Accounting Review, 2023)
ABSTRACT Fundamental to the accounting literature is that firms’ stock prices relate positively to their earnings news. We examine a setting where investors may be unsure to which firm the announced earnings accrue: earnings announced by acquisition targets between the announcement and completion of the acquisition. We find targets’ stock prices relate positively to their unexpected earnings during this interim period but only for unsuccessful M&A deals. For completed deals, we fail to find that targets’ or acquirers’ stock prices respond to targets’ unexpected interim earnings at the time of announcement. However, we find that targets’ interim earnings predict future returns of the combined firm following deal completion. A trading strategy based on targets’ interim earnings produces economically significant annualized abnormal returns of 7.25 percent. Our findings suggest investors respond inefficiently to the earnings that targets announce between the announcement and completion of acquisitions. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: M40; M41; G34.